The Development of E-Butler Hotel Service Robot - Benedick Clemons; Ignatius Ferdyan; Kevin Anderson (Bina Nusantara University, 2022)
A hotel is a place that provides accommodation, food, drink, and services for people traveling far from home. During this pandemic, many hotels started to apply strict health protocols for social distancing by reducing the number of their employees. For this purpose, we developed a service robot for some works in a hotel called E-butler. E -butler robots can provide amenities delivery service for the guest. The butler application for ordering amenities was developed by using MIT App Inventor as a prototype and will be developed further using Flutter. While the hardware of the E-butler robot is developed using the Mecanum wheels platform and Arduino for controlling the movement of the robot. Furthermore, the e-butler robot is equipped with teleconference devices based on Jetson Nano to facilitate communication between hotel employees and guests. Based on our evaluation, the butler robots can carry out the main task of E-butler, which can replace human butlers in hotels.